Development of an Exposition Writing Learning Model Based on Guided Group Investigation for Students of Class VIII of SMP in Gowa District - Andi Syamsul Alam (Universitas Muhammadiyah Enrekang, 2023)
This research is a development research that generally aims to describe the development of an exposition writing learning model based on guided group investigation for grade VIII students of SMP Negeri 1 Karunrung, Bajeng Barat District, Gowa Regency. The development method used follows the Four-D development design and the research design used is one group pretest-posttest. The collected data were analyzed descriptively quantitatively. The results of the study showed (1) Producing a valid guided group investigation-based exposition writing learning model for class VIII students of SMP Negeri 1 Karunrung, Gowa Regency with the steps as described in the design of the learning model that has been developed and also described in the RPP. (2) the implementation of the guided group investigation-based exposition writing learning form, especially the implementation of the RPP, was carried out well, namely in trial I it obtained an average score of 3.54, in trial II the average was 3.75, (3) student activities were carried out well, namely in trial I it obtained an average score of 3.59, in trial II, the average was 4.0, (4) the exposition writing learning outcome test was carried out well, namely in trial I, namely: in the pretest it produced 0.55 (unsuccessful), while in the posttest it increased to 0.86 (successful). Trial II, the pretest conducted resulted in 0.60 (unsuccessful), while in the posttest it increased to 0.88 (successful), (5) student responses to the developed learning model were carried out well, namely in trial I, responding happily, which was 78.78, in trial II, it increased to 97.56, and (6) obstacles encountered in both trials I and II, namely the class was less conducive, especially when forming groups, as well as when students conducted investigations. However, these obstacles can be handled well, so that the learning process continues as expected. From the results of the research conducted, it can be concluded that the developed learning model can improve learning outcomes in writing expositions, which also means that this learning model is very effective for use in learning to write expositions in junior high schools.